2014
DOI: 10.1002/ps.3810
|View full text |Cite
|
Sign up to set email alerts
|

Survey on whiteflies and their parasitoids in cassava mosaic pandemic areas of Tanzania using morphological and molecular techniques

Abstract: The accurate identification of natural enemies is an essential first step in developing effective biological control solutions for B. tabaci in Tanzania and the wider cassava-growing environments of Africa. The new data provided here represent an important contribution to this goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Although in this study they occurred in small numbers, they have been reported to colonize and co-exist on cassava and are known to cause low to moderate damage in this crop [ 72 ]. The spiralling whitefly has been reported from various countries across Africa [ 64 , 73 , 74 , 75 , 76 , 77 ]. Bondar’s nesting whitefly has been reported to colonize cassava in Uganda, Nigeria, and Tanzania [ 74 , 77 , 78 ] and was found in whitefly samples from cassava in coastal Kenya [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although in this study they occurred in small numbers, they have been reported to colonize and co-exist on cassava and are known to cause low to moderate damage in this crop [ 72 ]. The spiralling whitefly has been reported from various countries across Africa [ 64 , 73 , 74 , 75 , 76 , 77 ]. Bondar’s nesting whitefly has been reported to colonize cassava in Uganda, Nigeria, and Tanzania [ 74 , 77 , 78 ] and was found in whitefly samples from cassava in coastal Kenya [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-four species of Encarsia and 14 species of Eretmocerus , with Eretmocerus mundus Mercet and Encarsia sophia Girault and Dodd being the most dominant (Legg et al , 2003). Surveys of B. tabaci parasitoids in cassava in Tanzania identified using a molecular approach, ten species of parasitoids (Guastella et al , 2015). Hoelmer et al (1995) summarized several papers that suggested that parasitoids may be insufficient to control B. tabaci without other control methods.…”
Section: Biotic Factorsmentioning
confidence: 99%
“…A list of the parasitoids attacking the Bemisia genus in Sub-Saharan Africa included eight or more species, with Eretmocerus mundus Mercet (Hymenoptera: Aphelinidae) and Encarsia sophia Girault (Hymenoptera: Aphelinidae) and Dodd being the most often recorded (Legg et al, 2003). More recent surveys of B. tabaci parasitoids in cassava in Tanzania found 10 species of parasitoids (Guastella et al, 2015). Given that there are likely to be more parasitoid species present than currently recognized, we urgently need to use both morphological and molecular techniques to identify the parasitoid species diversity in this region and to determine the most numerically common species in order to focus future research on harnessing their naturally occurring biocontrol services.…”
Section: The Importance Of Local Production To Foster the Uptake Of Amentioning
confidence: 99%